USE OF PEDAGOGICAL SOFTWARE IN PEDAGOGICAL CLASSES - Sagdullayev Jahongir Ahmadjon o’g’li (Galaxy International Interdisciplinary Research Journal, 2021)
This article discusses the use of pedagogical technologies in the organization of training,education of a harmoniously developed generation in the spirit of universal and national values formed over the centuries, mastery of pedagogical and psychological methods, high level of professionalism and practical application of modern pedagogical and information and communication technologies. referred to as